A bidirectional Mendelian randomization study of sarcopenia-related traits and inflammatory bowel diseases - Jiao, Xin; Wu, Wen-yu; Zhan, Shao-feng; Liu, Jian-bo; Zhang, Xian-jin (Frontiers in Immunology, 2023)
Background There is increasing evidence pointing to a close relationship between sarcopenia and inflammatory bowel disease. However, it remains unclear whether or in which direction causal relationships exist, because these associations could be confounded. Methods We conducted a two-sample bidirectional mendelian randomization analysis using data from European genome-wide association studies of the appendicular lean mass(n = 450,243), walking pace(n = 459,915), grip strength (left hand, n = 461,026; right hand, n = 461,089), inflammatory bowel disease (25,042 patients and 34,915 controls), ulcerative colitis (12,366 patients and 33,609 controls), and Crohn’s disease (12,194 patients and 28,072 controls) to investigate the causal relationship between sarcopenia-related traits and inflammatory bowel disease and its subtypes on each other. The inverse-variance weighted method was used as the primary analysis method to assess the causality, and a comprehensive sensitivity test was conducted. Results Genetically predicted appendicular lean mass was significantly associated with inflammatory bowel disease (OR = 0.916, 95%CI: 0.853–0.984, P = 0.017), ulcerative colitis (OR =0.888, 95%CI: 0.813–0.971, P = 0.009), and Crohn’s disease (OR = 0.905, 95%CI: 0.820–0.999, P = 0.049). Similar results also revealed that the usual walking pace was causally associated with Crohn’s disease (OR = 0.467, 95%CI: 0.239–0.914, P = 0.026). Reverse mendelian randomization analysis results found that genetic susceptibility to inflammatory bowel disease, and Crohn’s disease were associated with lower appendicular lean mass. A series of sensitivity analyses ensured the reliability of the present research results. Conclusion The mendelian randomization study supports a bidirectional causality between inflammatory bowel disease, Crohn’s disease and appendicular lean mass, but no such bidirectional causal relationship was found in ulcerative colitis. In addition, genetically predicted usual walking pace may reduce the risk of Crohn’s disease. These findings have clinical implications for sarcopenia and inflammatory bowel disease management.